Public Transportation Line Passenger Prediction Using Mamdani Method of Fuzzy Logic to Foresee Holiday Passenger Surge - Elfira Makmur; Dessy Ana Laila Sari (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
This study aims to predict the number of passengers on the Mall Pannakkukang-Galesong Harbor route on the "Teman Bus" fast transit transportation system in Makassar City. Public transportation modes often face the problem of an imbalance between the number of buses and the number of passengers, which can reduce the comfort and efficiency of passenger mobility. To overcome this problem, this study uses a fuzzy logic approach, specifically the Mamdani fuzzy method, to predict the number of passengers who will take the bus based on input variable data that has been collected, such as day temperature and weather, as well as the output variable, namely the number of passengers. The results obtained in this study are based on the inputs given, namely the day with a value of 0.5 and the weather temperature with a value of 30. The number of passengers is 1500, which means the number of passengers is included in the quiet category.